Evaluating the effect of using shredded waste tire in the asphalt concrete-binder coarse on Marshall parameters - Elsa Eka Putri; Yosritzal Yosritzal; Akhyarul-An Agusyaini; Wiwik Budiawan (SINERGI, 2022)
Shredded Waste Tires are industrial materials that can be used in the asphalt mixture. The use of tires increases every day, considering the number of vehicles that grow from year to year. Using used tires is highly recommended for efforts to reduce waste that will harm the environment. The research aims to see the effect of adding shredded tires in a pavement mixture based on Marshall Value. The AC-BC pavement layer is not directly in contact with wheel load. Still, it must have sufficient thickness and stiffness to minimise stress or strain from traffic loads continuously transferred from the top of the pavement. The most important characteristic of the AC-BC is its stability. The optimum asphalt content value in the AC-BC mixture is 6.81%, mixed with various shredded waste tires. The Asphalt Concrete-Binder Course blended with 1.5%, 3.5%, 5.5% and 7.5% of the various shredded waste tire. The optimum shredded tire content was obtained at 3.5%, with the stability value increased by 2.1% from 1581.98 to 1614.88 kg, with a flow value of 5.43 mm, and a Marshall Quotient value of 297.4 kg/mm.